Maternal exposure to air pollutants, PCSK9 levels, fetal growth and gestational age – An Italian cohort. (April 2021) - Macchi, C.; Iodice, S.; Persico, N.; Ferrari, L.; Cantone, L.; Greco, M.F.; Ischia, B.; Dozio, E.; Corsini, A.; Sirtori, C.R.; Ruscica, M.; Bollati, V.
Highlights: In healthy pregnant women, circulating PCSK9 positively correlates with air pollutants. PCSK9 levels are associated to the outcomes of pregnancy occurring at delivery. A rise in PCSK9 levels associates to decreased gestational age at delivery. A rise in PCSK9 levels associates to an increased probability of urgent cesarean delivery. Abstract: Objective: Exposure to airborne pollutants during pregnancy appears to be associated with uterine growth restriction and adverse neonatal outcome. Proprotein convertase subtilisin/kexin type (PCSK9), the key modulator of low-density lipoprotein (LDL) metabolism, increases following particulate matter (PM10 ) exposure. Because maternal cholesterol is required for fetal growth, PCSK9 levels could be used to evaluate the potential impact of airborne pollutants on fetal growth. Design: A cohort of 134 healthy women during early pregnancy (11–12 weeks of gestational age) was studied. Results: A significant association between circulating PCSK9 levels and three tested air pollutants (PM10, PM2.5, nitric oxide (NO2 )) was found. Of importance, gestational age at birth was reduced by approximately 1 week for each 100 ng/mL rise in circulating PCSK9 levels, an effect that became more significant at the highest quartile of PM2.5 (with a 1.8 week advance in delivery date for every 100 ng/mL rise in circulating PCSK9; p for interaction = 0.026). This finding was supported by an elevation of the odds ratio for urgent cesarean delivery for each 100 ng/mL rise in PCSK9 (2.99, 95% CI, 1.22–6.57), similar trends being obtained for PM10 and NO2 . Conclusions: The association between exposure to air pollutants during pregnancy and elevation in PCSK9 advances our understanding of the unforeseen influences of environmental exposure in terms of pregnancy associated disorders.